(untitled) (American Journal of Research in Humanities and Social Sciences, 2025)
In textbooks and historical works of the Soviet era, there are many biased statements that the majority of residents of Turkestan were illiterate, and only two percent of the population could read and write. This article analyzes information about mudarris who taught in the madrassas of the Bukhara Emirate in the 19th-20th centuries.